New formulas for mixing test to discriminate between lupus anticoagulant and acquired hemophilia A. Issue 143 (July 2016) - Kumano, Osamu; Ieko, Masahiro; Naito, Sumiyoshi; Yoshida, Mika; Takahashi, Nobuhiko; Suzuki, Takeshi; Komiyama, Yutaka
Abstract: Introduction: Lupus anticoagulant (LA) is an antibody that interferes with in vitro coagulation reactions. The mixing test is considered useful for LA diagnosis and is also recommended to differentiate between acquired hemophilia A (AHA) and factor deficiency. However, there has been little study to differentiate between LA and AHA. Our aims are to investigate whether we can differentiate LA and AHA by the mixing test and to establish new formulas for the mixing test to differentiate these samples clearly. Materials and methods: We examined 27 LA-positive, 29 coagulation factor deficient, 24 unfractionated heparin and 48 AHA samples. Index of circulating anticoagulant (ICA) values, calculated from the clotting times without incubation and after 2 h incubation, were defined as ICA immediate (ICAi) and ICA delayed (ICAd) respectively. ICAd/ICAi and ICAd − ICAi were also calculated to compare the sensitivity and specificity. Results: ICAd/ICAi and ICAd − ICAi for AHA samples were significantly higher than those of the other sample groups. The sensitivities to AHA in ICAi, ICAd, ICAd/ICAi and ICAd − ICAi were 66.7%, 81.3%, 93.8% and 91.7% respectively, while the specificities for AHA were 45.0%, 66.3%, 85.0% and 98.8% respectively. ICAd/ICAi and ICAd − ICAi showed high sensitivity and specificity. Conclusions: ICAd/ICAi and ICAd − ICAi were useful for LA and AHA diagnosis, because these could differentiate between LA and AHA samples. These new formulas can contribute to the rapid diagnosis and treatment of LA and AHA. Highlights: The index of circulating anticoagulant (ICA) is recommended to show the results in the mixing test. The new formulas based on ICA could show the significant difference between LA and AHA. The new formulas can contribute to the rapid diagnosis and treatment of LA and AHA.